Determinants of exclusive breastfeeding continuity among mothers of infants under six months in Plateau State, Nigeria - Jacdonmi, Itse; Muhamad S., Suhainizam; Suriani, Ismail B.; Zoakah, Ayuba I.; Jacdonmi, Gbubemi R. (The International Journal of Health Sciences and Research, 2016)
Introduction: Exclusive breastfeeding practice is of public health significance as it improves child health and growth. This study was aimed at determining factors associated with exclusive breastfeeding practices among mothers of infants under six months. Materials and Methods: This was a cross-sectional study. 310 mother-infant pairs were selected from three primary health care facilities in Jos North LGA. A validated questionnaire was administered to mothers. Main outcome measures were factors associated with exclusive breastfeeding practice.